Initial stage of the beam-plasma discharge in helium: simulation via PIC method - Kosarevych, B.P.; Soloviova, M.J.; Anisimov, I.O. (Вопросы атомной науки и техники, 2013)
Initial stage of the beam-plasma discharge (BPD) in Helium was studied using 1D simulation via particle-in-cell method. Several regimes were observed and described depend on ranges of beam current density and gas pressure: absence of BPD ignition, BDP ignition with the small degree of additional ionization, and “regular” BPD mode with the significant heating of the background plasma electrons by the beam-plasma instability HF field. Исследована начальная стадия развития плазменно-пучкового разряда (ППР) в гелии с помощью одномерного компьютерного моделирования методом крупных частиц. В зависимости от плотности тока пучка и давления газа в системе наблюдалось три характерных режима: отсутствие зажигания ППР; зажигание ППР с малой дополнительной ионизацией; “регулярный” режим ППР, сопровождающийся заметным нагревом электронов фоновой плазмы высокочастотным электрическим полем плазменно- пучковой неустойчивости. Досліджено початкову стадію розвитку плазмово-пучкового розряду (ППР) у гелії шляхом одновимірного комп’ютерного моделювання методом макрочастинок. Залежно від густини струму пучка та тиску газу в системі виявлено три характерних режими: відсутність запалювання ППР; запалювання ППР з малою додатковою іонізацією; “регулярний” режим ППР, що супроводжується помітним розігрівом електронів фонової плазми високочастотним електричним полем плазмово-пучкової нестійкості.